Low-temperature growth of silicon nanotubes and nanowires on amorphous substrates - Mbenkum, Beri Nsoyani; Schneider, Andreas S.; Schütz, Gisela; Xu, C.; Richter, Gunther; Aken, Peter A. van; Majer, Günter; Spatz, Joachim P. (ACS nano, 2010)
Silicon one-dimensional (Si 1D) materials are of particular relevance due to their prospect as versatile building materials for nanoelectronic devices. We report the growth of Si 1D structures from quasi-hexagonally ordered gold (Au) nanoparticle (NP) arrays on borosilicate glass (BSG) and SiOx/Si substrates. Using hydrogen instead of oxygen plasma during NP preparation enhances the catalytic activity of AuNPs (diameters of 10−20 nm), enabling Si 1D growth at temperatures as low as 320 °C. On BSG, Si nanowires (SiNWs) are identified and reasonable vertical alignment is achieved at 420 °C. On SiOx/Si, only Si nanotubes (SiNTs) are obtained right up to 420 °C. A mixture of SiNTs and SiNWs is observed at 450 °C and only SiNWs grow at 480 °C.
Gesehen am 12.04.2023